Fentanyl use disorder characterized by unprescribed use of transdermal patches: a case report. Issue 2 (3rd April 2022) - Guliyev, Cavid; Tuna, Zehra Olcay; Ögel, Kültegin
Abstract: Background: Fentanyl is a synthetic opioid with analgesic potency 75–100 times higher than that of morphine, and its analgesic effect is used for pain treatment, mostly in cancer patients. Using fentanyl patches may reduce misuse potential due to the transdermal route of administration, long-acting action, sustained release delivery property, and maintenance of steady-state serum concentration of the drug. Although there have been reports of transdermal fentanyl patches (TFPs) misuse via transmucosal, trans-nasal, intravenous, and oral routes of administration, fentanyl use disorder via the transdermal route is very rare. Case: In this case report, we present a patient with a history of substance use disorder who developed fentanyl use disorder via transdermal route after using unprescribed TFP in order to quit opium gum. The CARE guidance was followed in the preparation of this case report. Conclusion: The risk of use disorder may be higher, especially in individuals with a history of substance use disorders. This risk should be taken into account when clinicians prescribe this medication.